Structure-switching M3L2 Ir(iii) coordination cages with photo-isomerising azo-aromatic linkers12. Issue 42 (6th September 2018) - Oldknow, Samuel; Martir, Diego Rota; Pritchard, Victoria E.; Blitz, Mark A.; Fishwick, Colin W. G.; Zysman-Colman, Eli; Hardie, Michaele J.
Abstract : Deep-blue luminescent [Ir(C^N)2 3 (L)2 ] 3+ coordination cages with structurally integral pyridyl-azo-phenyl groups can be reversibly photo-isomerised with no compositional change. Abstract : Cyclotriguaiacylene has been functionalised with 3- or 4-pyridyl-azo-phenyl groups to form a series of molecular hosts with three azobenzene-type groups that exhibit reversible photo-isomerisation. Reaction of the host molecules with [Ir(C^N)2 (NCMe)2 ] + where C^N is the cyclometallating 2-phenylpyridinato, 2-(4-methylphenyl)pyridinato or 2-(4, 5, 6-trifluorophenyl)pyridinato results in the self-assembly of a family of five different [Ir(C^N)2 3 (L)2 ] 3+ coordination cages. Photo-irradiation of each of the cages with a high energy laser results in E → Z photo-isomerisation of the pyridyl-azo-phenyl groups with up to 40% of groups isomerising. Isomerisation can be reversed by exposure to blue light. Thus, the cages show reversible structure-switching while maintaining their compositional integrity. This represents the largest photo-induced structural change yet reported for a structurally-integral component of a coordination cage. Energy minimised molecular models indicate a switched cage has a smaller internal space than the initial all- E isomer. The [Ir(C^N)2 (NCMe)2 ] + cages are weakly emissive, each with a deep blue luminescence at ca. 450 nm.